(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
Sala de espera was an exercise in forced loneliness and nostalgia, where the reference point that allowed the reinstallation of the poetic voice and the vital impulse was the first material of that same voice: the word, the word in Spanish. Thus, for Max Aub, the break was neither radical nor passive. The title of the magazine reflects a deep faith; of a conviction of change, where everything seems to have stopped.